Reflujo gastroesofágico y su relación con el cáncer de esófago - Vinueza Barrionuevo, Nelly Tatiana (2025)
Gastroesophageal reflux (GERD) is a chronic and recurring medical condition characterized by the involuntary and repeated return of acidic stomach contents into the esophagus while esophageal cancer (EC) is a malignant disease that affects the esophagus, a muscular tube that connects the throat to the stomach and the relationship between gastroesophageal reflux and esophageal adenocarcinoma, has raised concerns due to accumulating evidence indicating that GERD may predispose and increase the risk of malignancy. Objective: to conduct an updated bibliographic review of the relationship and mechanism of action between GERD and esophageal cancer to improve the quality of prevention and health promotion strategies in the population. Methodology: a descriptive study was carried out through a bibliographic review, in which various scientific sources were examined, including results of various research, linked to the topic in question and that clearly demonstrate the existence of this problem. Results: several articles indicate a causal relationship between gastroesophageal reflux and esophageal cancer, adding in certain cases intermediary factors to these, but with the presence or absence of these, GERD may continue to be the most pre-determining factor of EC. Conclusions: This review indicates that the studies carried out on the relationship between GERD and esophageal cancer demonstrate a positive relationship with several important factors such as: chronic esophagitis, Barrett's esophagus, age and duration of the clinical manifestations of GERD.